2017
DOI: 10.1093/cid/cix598
|View full text |Cite
|
Sign up to set email alerts
|

Plasma But Not Cerebrospinal Fluid Interleukin 7 and Interleukin 5 Levels Pre–Antiretroviral Therapy Commencement Predict Cryptococcosis-Associated Immune Reconstitution Inflammatory Syndrome

Abstract: High plasma IL-5 and IL-7 levels pre-ART were associated with increased risk of developing C-IRIS. High IL-5 levels may reflect a Th2 environment associated with impaired clearance of cryptococci while high IL-7 levels may reflect IL-7/IL-7R pathway dysfunction in T cells, both of which could be associated with C-IRIS immunopathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
0
16
0
2
Order By: Relevance
“…Figure 1 shows the time line of antifungal therapy, ART, C-IRIS events, and sample collection. Comparative demographic details of the original cohort of 130 participants and current substudy are found in Chang et al [ 5 ] and Akilimali et al [ 14 ] respectively, where the C-IRIS group and the control group without neurological deterioration showed no significant difference in age, gender, baseline HIV viral load, or serum cryptococcal antigen titers.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the time line of antifungal therapy, ART, C-IRIS events, and sample collection. Comparative demographic details of the original cohort of 130 participants and current substudy are found in Chang et al [ 5 ] and Akilimali et al [ 14 ] respectively, where the C-IRIS group and the control group without neurological deterioration showed no significant difference in age, gender, baseline HIV viral load, or serum cryptococcal antigen titers.…”
Section: Resultsmentioning
confidence: 99%
“…Electronic health records and big data platforms that can integrate genetic, immunologic, clinical, microbial, and environmental variables also hold promise as tools to integrate patient and microbial characteristics and identify measures that correlate with defined clinical and microbial states. Even today, clinical parameters, fungal burden, immunological measures, and cytokine perturbations that correlate with HIV-associated cryptococcosis [29][30][31][32][33] may provide insight into where a patient may lie on the parabola.…”
Section: Finding a Place On The Curvementioning
confidence: 99%
“…When it comes to preventing paradoxical C‐IRIS, sufficient and effective antifungal treatment plays an irreplaceable role, because higher residual Cryptococcus burden and related marks such as CRP and IL‐5 indicate higher C‐IRIS incidence . The most simple way to achieve a lower fungal burden before ART is to elongate the antifungal treatment, that is, delaying the initiation of ART.…”
Section: Cryptococcus‐related Immune Reconstitution Inflammatory Syndmentioning
confidence: 99%